Pengaruh Kompensasi, Lingkungan Kerja dan Stres Kerja terhadap Produktivitas Kerja : (Studi Kasus pada RS Bhayangkara TK. II Kota Kediri) - Wildan Anwar Adi Wibowo; Indah Yuni Astuti; Iing Sri Hardiningrum (Jurnal Manajemen Bisnis Digital Terkini, 2025)
Hospitals are a crucial sector in a country due to their functions encompassing various aspects of healthcare provision. Factors supporting smooth operations and quality healthcare services in hospitals include human resources, facilities and infrastructure, health information systems, financial management, good customer service, security, occupational health, and other supporting factors. This study aims to determine the effect of compensation, work environment, and work stress on employee work productivity at Bhayangkara Level II Hospital in Kediri City. The research method used is a quantitative approach with multiple linear regression analysis techniques. The sample in this study amounted to 40 respondents who were employees of Bhayangkara Level II Hospital in Kediri City. The results of the analysis show that partially compensation, work environment, and work stress have a positive and significant effect on employee work productivity. Compensation has a calculated t value of 2.500 with a significance of 0.015, work environment is 6.170 with a significance of <0.001, and work stress is 5.305 with a significance of <0.001. Simultaneously, these three variables also have a significant effect on work productivity with a calculated F value of 35.438 and a significance of <0.001. Based on these findings, it is recommended that the hospital management continue to evaluate the compensation system, create a conducive work environment, and manage employee work stress through training and counseling facilities. Further research is expected to add other variables such as internal communication, job satisfaction, and career development to obtain more comprehensive results.